Evaluating the isotopic niche of beaked whales from the southwestern South Atlantic and Southern Oceans - Riccialdelli, Luciana (2017)
The study of species’ niches is becoming increasingly important in ecological research with the growing need to understand how species and their habitat respond to rapid environmental changes. This kind of study is especially challenging in the case of oceanic and cryptic species such as beaked whales. We analyzed δ13C and δ15N values in bone collagen to study interspecific variation in the isotopic niche of 8 species of beaked whales (Berardius arnuxii, Hyperoodon planifrons, Mesoplodon bowdoini, M. grayi, M. hectori, M. layardii, Tasmacetus shepherdi and Ziphius cavirostris) that stranded along the coast of Tierra del Fuego, Argentina, between 1967 and 2009. We found a spatial (e.g. feeding areas) and trophic (e.g. diet) isotopic segregation among these species, which are known to inhabit subantarctic to Antarctic waters. Isotopic analysis showed that, while spatial segregation seems to operate to a higher degree in species of the same genus (e.g. Mesoplodon), trophic differentiation allowed the co-existence of sympatric species from different genera (e.g. Ziphius, Hyperodoon and Mesoplodon). Our results agree with previous studies based on stomach content analyses. In addition to different trophic strategies, variation in habitat preferences were also revealed by stable isotope analysis. An isotopic trend in both δ13C and δ15N values was found among beaked whales and possible prey species in accordance with previous information on other cetacean species known to have feeding areas in different ocean regions. The present study provides valuable ecological information about elusive and littlestudied beaked whale species inhabiting the world’s southernmost oceans.